Establishment of immunological methods for the detection of soybean proteins in surimi products. Issue 1 (November 2015) - Jiang, Tao-Ling; Cai, Qiu-Feng; Shen, Jian-Dong; Huang, Ming-Jie; Zhang, Ling-Jing; Liu, Guang-Ming; Cao, Min-Jie
Abstract Recently, adulteration by adding soybean proteins to surimi products to replace fish muscle has been gaining momentum. In this study, soybean trypsin inhibitor (STI) was chosen as target protein for detection of soybean proteins in surimi products and both polyclonal antibody and monoclonal antibody (A11-6) against STI were prepared. A semi-quantitative means of analyzing soybean proteins in various commercial surimi products was performed by Western blot. A sandwich enzyme-linked immunosorbent assay (s-ELISA) was further developed to quantitatively detect soybean proteins in surimi products. The limit of detection (LOD) and the limit of quantification (LOQ) were 0.68 μg SPI/mL (13.6 mg SPI/kg food) and 3.09 μg SPI/mL (61.7 mg SPI/kg food), respectively. The rates of recovery of soybean proteins ranged from 100.1% to 122.2%, and the coefficient of variation (CV) was less than 4.1%. Our results indicated that the methods established can be applied to monitor soybean proteins in surimi products.